2017
DOI: 10.1186/s12884-017-1364-y
|View full text |Cite
|
Sign up to set email alerts
|

The magnitude and correlates of Parvovirus B19 infection among pregnant women attending antenatal clinics in Mwanza, Tanzania

Abstract: BackgroundHuman parvovirus B19 (B19) infection has been associated with congenital infection which may result into a number of the adverse pregnancy outcomes. The epidemiology and the magnitude of B19 infections among pregnant women have been poorly studied in developing countries. This study was done to establish preliminary information about the magnitude of B19 among pregnant women attending antenatal clinics in the city of Mwanza, Tanzania.MethodsA cross-sectional study was conducted between December 2014 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 25 publications
(20 reference statements)
4
14
0
1
Order By: Relevance
“…The results regarding seroprevalence for antibodies against parvovirus B19 from Mexico, Brazil, Germany, Poland and Turkey ranging from 36 to 55% are broadly consistent with earlier reports from India, Tanzania, Iran and Japan [35][36][37][38]. A study by Mossong et al determined age-specific anti-B19 seroprevalence profiles in five European countries (Belgium, England and Wales, Finland, Italy, Poland) by testing blood samples from large serum banks for the presence of IgG antibodies against parvovirus B19 using the same assay for all samples [39].…”
Section: Parvovirus B19supporting
confidence: 90%
“…The results regarding seroprevalence for antibodies against parvovirus B19 from Mexico, Brazil, Germany, Poland and Turkey ranging from 36 to 55% are broadly consistent with earlier reports from India, Tanzania, Iran and Japan [35][36][37][38]. A study by Mossong et al determined age-specific anti-B19 seroprevalence profiles in five European countries (Belgium, England and Wales, Finland, Italy, Poland) by testing blood samples from large serum banks for the presence of IgG antibodies against parvovirus B19 using the same assay for all samples [39].…”
Section: Parvovirus B19supporting
confidence: 90%
“…Though the prevalence of B19V among pregnant women in developing countries is not well documented, few available documents show a sero-prevalence of 3.3% for B19V IgM in South Africa (Mirambo et al, 2017), 32.8% in Tanzania (Mirambo et al, 2017) and 13.2% in Central Nigeria (Emiasegen et al, 2011). A prevalence of 24.9% for B19V IgG has been documented in South Africa, 55.0% in Tanzania (Mirambo et al, 2017), 27.5% in Central Nigeria (Emiasegen et al, 2011) and 20% in South-West Nigeria (Abiodun et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding RV, 1.2% of studied women had an acute infection, which is comparable to a previous study in the same settings that reported an IgM seropositivity of 0.3% among asymptomatic pregnant women [ 42 ]. This unexpected low seropositivity in the current study could be explained by the fact that signs and symptoms of acute RV infections are nonspecific, and most of the time, they mimic those of other viruses, which have been reported to be common in Mwanza [ 6 , 43 , 44 ]. In addition, the majority of the women enrolled in this study were reported to have signs and symptoms whereby some of them might have occurred a long time before sample collection.…”
Section: Discussionmentioning
confidence: 50%